Place, placelessness, insideness, and outsideness in John Sayles' Sunshine State - Seamon, David (My University, 2009)
John Sayles is one of America's most successful independent filmmakers, whose works include "Return of the Secaucus Seven" (1980), "City of Hope" (1991), and "Lone Star" (1996). This article examines Sayles' portrait of place in "Sunshine State" (2002), a film set in Plantation Island, Florida, where large-scale corporate development is transforming two communities- one black, the other white - into upscale winter resorts. Sayles' film probes the place experience of some sixteen vividly drawn characters and illuminiates how the same physical place, for different individuals and groups, can evoke a broad spectrum of situations, meanings, and potential futures. One of Sayles" conclusions is that people cannot escape the place in which they find themselves. They can, however, learn from that place and thereby decide wheter and in what ways they will offer that place commitment or not.
Keywords: Sayles, John; Place; Phenomenology of place; Phenomenology of film; Landscapes of globalization; Placelessness; Florida